How to best handle vaccine decliners: scientific facts and psychological approach. Issue 1162 (9th April 2021) - Xantus, Gabor Zoltan; Burke, Derek; Kanizsai, Peter
Abstract: There is currently no curative drug therapy for COVID-19. The spread of the virus seems relentless despite the unprecedented epidemiological measures. Prevention remains the only feasible option to stop the pandemic; without population-level vaccination, we are unlikely to regain the quality of social life and the unrestricted economy/commerce we enjoyed before. Anti-vaxxers and conspiracy theorists are seemingly oblivious to the detrimental effect of COVID-19 both at an individual and societal level. These groups have (and probably will) continue to attempt to undermine efforts to eradicate the virus despite the fact that the major reduction in morbidity/and mortality of infectious diseases of the past century was achieved through the development of vaccines and improved hygiene. Conspiracy theories are directly associated with reduced vaccine uptake and unfortunately neither anti-vaxxers nor vaccine hesitants cannot be persuaded (debunked) with logical arguments; hence, prescribers must not only be aware of the truth underlying the dense web of misinformation but must fully understand the psychological aspects as well to be able to efficiently counsel about the potential benefits and harms. Such knowledge is pivotal to help the lay public to make informed decisions about SARS CoV-2 in general and vaccination in particular; as the COVID-19 situation can probably be best controlled with mass inoculation and novel immune therapies. The lessons learnt regarding the importance of efficient communication and the adherence to the proven epidemiological measures hopefully would be leaving us better prepared for the future if challenged by novel communicable diseases of pandemic potential.